Correlative imaging for polymer science. Issue 12 (7th April 2021) - Wang, Yuyang; Friedrich, Heiner; Voets, Ilja K.; Zijlstra, Peter; Albertazzi, Lorenzo
Abstract: The characterization of polymeric materials is key towards the understanding of structure–activity relations and therefore for the rational design of novel and improved materials for a myriad of applications. Many microscopy techniques are currently used, with electron microscopy, fluorescence microscopy, and atomic force microscopy being the most relevant. In this perspective paper, we discuss the use of correlative imaging, that is, the combination of multiple imaging methodologies on the same sample, in the field of polymeric materials. This innovative approach is emerging as a powerful tool to unveil the structure and functional properties of biological and synthetic structures. Here we discuss the possibilities of correlative imaging and highlight their potential to answer open questions in polymer science. Abstract : In this Perspective, the use of correlative imaging is reviewed in the field of polymeric materials. This innovative approach is emerging as a powerful tool to unveil the structure and functional properties of biological and synthetic structures. The possibilities of correlative imaging and its potential in polymer science are outlined.